2003
DOI: 10.2307/3181062
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception of Emergency Contraception among Female Nigerian Undergraduates

Abstract: There is an urgent need to educate Nigerian young people about emergency contraception, emphasizing available methods and correct timing of use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
76
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(92 citation statements)
references
References 0 publications
13
76
3
Order By: Relevance
“…This is not different from previous studies [2,9]. Good knowledge of EC was a significant predictor of their use, which is in agreement with reports of studies conducted in Nigeria [11]. It has been suggested that millions of unwanted pregnancies could be prevented if emergency contraceptives were used [12].…”
Section: Discussionsupporting
confidence: 82%
“…This is not different from previous studies [2,9]. Good knowledge of EC was a significant predictor of their use, which is in agreement with reports of studies conducted in Nigeria [11]. It has been suggested that millions of unwanted pregnancies could be prevented if emergency contraceptives were used [12].…”
Section: Discussionsupporting
confidence: 82%
“…It is necessary to ensure dissemination of correct and appropriate information through these media in order to be certain that same passes to the end users. Friends and other peer groups have been consistently shown to be sources of information on reproductive health issues especially among young persons [18][19][20] and abortion care seekers 1 . It is necessary that these groups of people are especially targeted in awareness campaigns as a contraceptive wise adolescent would grow to be reproductive health wise adult.…”
Section: Discussionmentioning
confidence: 99%
“…This is at variance with reports from previous studies were health personnel contributed little to sources of awareness of contraception. 15,16 This therefore raises the issue of the content of information passed to clients on contraception and contraceptive usage by the health personnel in this community. Their level of training in contraceptive services and how effectively they were able to convey relevant information to their clients was identified to be poor; hence one of the interventions that were undertaken was training and strengthening the capacity of the health personnel in this community following an early qualitative study.…”
mentioning
confidence: 99%